2009
DOI: 10.1136/hrt.2009.174201
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of the Niigata-Chuetsu earthquake in Japan on acute myocardial infarction mortality: an analysis of death certificate data

Abstract: The Niigata-Chuetsu earthquake significantly increased long-term mortality from AMI in both men and women. Clinicians and policymakers in public health must recognise the need for long-term prevention of AMI in earthquake disaster areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 17 publications
5
35
2
Order By: Relevance
“…It has been reported that AMI mortality increased for 8 weeks after the H-A Earthquake, 5 in comparison with previous earthquakes, including the Northridge Earthquake. 17 The Northridge Earthquake was also an underground-type and was the same type as the H-A Earthquake, though damage was less than the H-A Earthquake. The GEJ Earthquake caused more severe damage and approximately 3-fold more human causalities as the H-A Earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AMI mortality increased for 8 weeks after the H-A Earthquake, 5 in comparison with previous earthquakes, including the Northridge Earthquake. 17 The Northridge Earthquake was also an underground-type and was the same type as the H-A Earthquake, though damage was less than the H-A Earthquake. The GEJ Earthquake caused more severe damage and approximately 3-fold more human causalities as the H-A Earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…43) Study limitations: The present study has several limitations. First, it was a single-center retrospective observational study.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this resistance may be explained by the central neural circuitry responsible for the interaction between emotion and exacerbation of asthma (17); this circuitry is thought to be different from the inflammatory immune system. During or after catastrophic events, in patients influenced by disasters, the control of chronic diseases, such as hypertension or diabetes, worsens for a relatively long period (3,5,18). For instance, an increase in AMI incidence was reported after the Great Hanshin earthquake (19).…”
Section: Discussionmentioning
confidence: 99%